ANALISIS METODE NILAI HASIL (EARNED VALUE) MENGGUNAKAN SIMULASI MONTE CARLO UNTUK MONITORING PROYEK PEMBANGUNAN JALAN - Kamila Salsabila Iman; Zetta Rasullia Kamandang (LPPM Universitas Abdurrab, 2024)
Project performance is assessed based on schedule, cost, and quality. Time and cost measurements must be carried out regularly to identify if there is a discrepancy with the plan. In the XYZ road construction project in East Java Province, a deviation of 20.707% was found in the 19th week, so it is necessary to analyze the concept of the value of results to determine the future development of the project. To analyze the spread of project uncertainty, Monte Carlo simulation is used by modeling the system with random numbers. The random number generated is the number between the minimum and maximum RAB for each type of work in the project. After repetition according to the number of iterations obtained with a relative error value of 2%. Then the frequency graph and normal distribution are analyzed, so it can be seen that the project must provide costs of Rp 11,031,591,805.11, Rp 16,742,117,603.03, and Rp 21,981,246,725.01 for performance evaluation at 50%, 75%, and 100% performance reviews. The SPI calculation result in week 19 is 0.409, indicating that the project is behind schedule. In addition, the TE calculation shows this project can be completed in 508 days or 73 weeks.